Delayed tooth replantation following root canal filling with calcium hydroxide and MTA: Histomorphometric study in rats - Esteves, Jônatas Caldeira; Marão, Heloisa Fonseca [UNESP]; Silva, Pedro Ivo dos Santos; Poi, Wilson Roberto [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Ribeiro, Eduardo Dias [UNESP]; Sonoda, Celso Koogi [UNESP] (Elsevier B. V., 2015)
The aim of this study was to perform a histomorphometric evaluation of the repair process in rat teeth replanted after root canals were filled with calcium hydroxide (CH) and mineral trioxide aggregate (MTA). Upper right incisors were extracted from 30 rats divided into three groups (n=10). The teeth were stored dry for 60min, after which the pulp and periodontal ligament (PDL) were removed and immersed in acidulated-phosphate sodium fluoride solution. In Group I, the root canals were filled with saline; in Group II, they were filled with CH; and in Group III, they were filled with CH, and the foramen was sealed with an MTA plug. The teeth were replanted, and the animals were sacrificed after 60 days. The sections with teeth were removed for histological preparation (haematoxylin and eosin, H&E). The characteristics of the PDL, cementum, dentine, and alveolar bone, as well as the occurrence of inflammatory and replacement root resorption and apical sealing, were subjected to histological and morphometric analysis (P<0.05). Group I was the most affected by root resorption (mean=67.05%). In Groups II and III, the resorption averaged 42.2% and 11.7%, respectively. Group III was less affected by inflammatory resorption and presented more areas of apical sealing by mineralized tissue (P<0.05). An apical MTA plug improved the repair of the replanted tooth by decreasing surface resorption and repairing mineralized tissue in the periapical region.
Keywords: Calcium hydroxide; Mineral trioxide aggregate; Periodontal ligament; Root resorption; Tooth replantation